The Limits of the Powers of the Central Bank in Slovakia (Liability for Damage Caused by a National Central Bank in the EU) - Čunderlík, L’ubomír (Maastricht 30: A Central European Perspective, 2025)
This chapter is devoted to the legislative and jurisprudential influences on the status and powers of the national central bank in the EU, in general, and in Slovakia, in particular. First, the aim is to present the substantive Slovak legal limits on the central bank’s powers and the European legal limits on the central bank’s powers in the EU. Regarding EU law, the chapter focuses on the execution of some of the tasksentrusted to the European Central Bank in the supervision of credit institutions, namely, on assessing the practice of the electronic filing of applications by banks in the case of licensing procedures under the Single Supervisory Mechanism, in the context of the relevant Slovak legislative framework (Act on Banks). The last part of this chapter will provide an analysis and assessment of the appropriateness of the current legal status of the liability the central bank in the Slovak Republic has for the exercise of public authority. This will be done in the light of a recent decision of the Court of Justice of the European Union. Following that, the conclusion presents some doubts of the author about the compatibility of Slovak legislation with EU law concerning the liability for damage caused by a national central bank. Based on the above, the Slovak concept of liability is potentially contrary to the prohibition of monetary financing of the public sector and represents a threat to the financial independence of the central bank in Slovakia.Keywords: Central bank, independence of central banks, legal convergence, liability for damage, prohibition of monetary financing